Moving forward with blended learning (BL) as a pedagogical alternative to traditional classroom learning - Dzakiria, Hisham (Malaysian Educational Technology Association (META), 2006)
Globalisation and technology are altering our views on education and educational offerings.Technology has given birth to many new avenues for learning. To name a few, online learning,teleconferencing, the Internet, computer assisted learning (CAL), web-based distance learning (WBDL) and other technologies currently exist. In turn, they have helped to coin the term “blended learning” (BL), and although the term is still ill-defined, BL has entered into the training and education scene and is gaining popularity. BL is no longer a fad but is now expanding and getting established, although rapidly changing. When an institution makes the critical choice of delivery methods, it needs to consider various factors. One in particular that this article advocates is the need to understand the students as the primary educational client, their perspectives and experiences, and the learning support mechanism for effective learning outcomes. This qualitative study reports in some detail the experiences of a small group of postgraduate learners as they progress through their Masters and Ph.D. courses at Universiti Utara Malaysia (UUM), Malaysia. The paper looks at learning as described by the learners – it is their story, their experiences and their perspective on graduate learning experiences at the institution. In particular, this paper looks at BL and what that entails to the learners. From these findings, conclusions have been drawn regarding the role of learning support to facilitate BL and the provision of better educational experiences and outcomes at UUM. This article offers several suggestions and a discussion on the broader applications of the BL framework and the readiness of the UUM students for its implementation.